Effect of silicon application on growth and yield of tomato (Lycopersicon esculentum Mill.) Var. Rajitha grown under water stress - Subhashini, H.P.S.; Silva, C.S.D.; Silva, N.R.N. (University of Jaffna, 2021)
This experiment was aimed to determine the effect of application of silicon on the growth and yield of tomato (var. Rajitha) under water stress condition. Treatments of the experiment were 75 mg of Si and no water stress (T1), 75 mg of Si and 50% water stress (T2), 150 mg of Si and no water stress (T3), 150 mg of Si, and 50% water stress (T4), no Si and no water stress (T5), and no Si and 50% water stress (T6). A pot experiment was conducted at a plant house in Horticultural Crop Research and Development Institute, Gannoruwa in 2019. The experiment was conducted as a Complete Randomized Design with a factorial treatment structure. There were 5 replicates in each treatment. Water stress and silicon were taken as main factors. Silicon was added as magnesium silicate and water stress was imposed by maintaining a moisture level equivalent to 50% of field capacity. According to the results, the significantly highest (p ≤ 0.05) mean height of plants (132.6 cm) in (13 weeks after planting) was observed in plants of T3 treatment, and the lowest mean height (107cm) was observed in plants of T6 treatment. Among the water stress treatments, T4 treatment reported significantly highest (p ≤ 0.05) shoot/ root ratio followed by T2 treatment. The application of magnesium silicate had improved yield parameters such as number of flowers, number of fruits, fruit weight, and fruit yield. In water stress treatments, T4 plants showed the highest flowering. Among the water stress treatment plants T4 resulted in the highest number of fruits per plant (13.6). Water stress negatively affects fruit weight but compared to T6 treatment plants (54.4 g) T2 treatment plants (55.7 g) and T4 treatment plants (56.3 g) showed higher fruit weight, but the treatments were not significantly different from each other. Lower fruit yield was observed in T6 treatment plants (0.707 kg) but T2 treatment plants (0.77 kg) and T4 treatment plants (0.967 kg) have shown higher fruit yield. The results of this experiment showed that the water stress reduced the growth of tomato plant and yield. But the application of magnesium silicate has a positive influence on growth and yield by enhancing the water tolerance of tomato under water stress conditions.
Keywords: Growth parameters; Nutritional parameters; Silicon; Tomato; Water stress; Yield parameters